CAM20u: An extension of CAM16 for predicting the color appearance of unrelated colors. Issue 4 (20th January 2021) - Gao, Cheng; Li, Changjun; Shi, Keyu; Luo, Ming R.; Pointer, Michael R.
Abstract: A comprehensive color appearance model should be capable of predicting color appearance under a wide range of viewing conditions, including related and unrelated colors. The current CAM16 model was designed to predict the appearance of related colors and is in the process of becoming a CIE recommendation, to replace the current CIECAM02 model. This article describes an extension of CAM16 (named CAM20u) for predicting the brightness, hue quadrature, amount‐of‐white, and colorfulness attributes of unrelated colors. Its performance, together with that of other unrelated models, was tested based on the three available datasets. The results show that the CAM20u model significantly outperforms the others, especially for colorfulness and amount‐of‐white.